Compassionate love parenting training to reduce stress in caregivers of children with special needs: An experimental study - Desiningrum, Dinie Ratri; Hermawati, Donna; Somantri, Maman; Indriana, Yeniar; Rusydana, Alhimna (Psikohumaniora: Jurnal Penelitian Psikologi, 2023)
Caregivers of children with special needs experience a high workload, which causes stress and low quality of life. A compassionate love attitude amongst caregivers is needed to improve the quality of parenting. This study aims to develop a compassionate love parenting training program to reduce stress among children with special needs caregivers. The method employed was Pre-experimental Design, with One-group Pre-test-Post-test. The research participants were 40 caregivers identified using the purposive sampling technique. In the pre-test, the stress level of the caregivers was measured using the Parental Stress Scale with 24 items (α = .828). The data were analyzed using the Wilcoxon test to observe the differences between the pre-test and post-test of two dependent samples. The results show that the stress score decreased significantly, with Z = -2.023 and with a significance level of .043 < .05. It is demonstrated that regular training in compassionate love parenting reduced the stress felt by caregivers of children with special needs. The implementation of compassionate love parenting training in special needs therapeutic centers is important, as it is one of the intervention methods that has been proven to reduce the level of stress to optimize the growth of the child.